El espíritu del tiempo en las ciudades y en sus libros (2013)
From the re-release of the book by Jane Jacobs, The Death and Life of Great American Cities in 2011, fifty years after its first publication, questions about Colombian cities arise such as: what happened in those cities, in the Colombian context and Colombians during those fifty years? Why are Jane Jacobs’ questions, although referring to a model of the postwar American city, still valid in our context? This approaches a method to get into the spirit of the times, working with books and texts about the city that allow discovering in them the “spirit of time”. Hence this work emerges under the hypothesis: the moments of articulation and change in the continuity of history can be identified through certain texts which impacted the spirit of time, and this is mediated through a second hypothesis explaining the research meaning and its goals: the completion of research comes from the interpretation of texts in light of the spirit of time and the local conditions. So it can be established that the spirit of the Colombian urban environment experienced a strong influence of the so-called postmodern authors who questioned the breaking of forms, uses and meanings of the traditional city in projects of modern architecture and urbanism. In the nineties the urban environment spirit in Colombia got closer to philosophical debates and narratives through analysis categories not covered by modern urbanism